The Role of Nuclear Fragmentation in Particle Therapy and Space Radiation Protection - Zeitlin, Cary; La Tessa, Chiara (Frontiers in Oncology, 2016)
The transport of so-called HZE particles (those having high charge, Z, and energy, E) through matter is crucially important both in space radiation protection and in the clinical setting where heavy ions are used for cancer treatment. Transport physics is governed by two types of interactions, electromagnetic (ionization energy loss) and nuclear. Models of transport such as those used in treatment planning and space mission planning must account for both effects in detail. The theory of electromagnetic interactions is well developed, but nucleus-nucleus collisions are so complex that no fundamental physical theory currently describes them. Instead, interaction models are generally anchored to experimental data, which in some areas are far from complete. The lack of fundamental physics knowledge introduces uncertainties in the calculations of exposures and their associated risks. These uncertainties are greatly compounded by the much larger uncertainties in biological response to HZE particles. In this article, we discuss the role of nucleus-nucleus interactions in heavy charged particle therapy and in deep space, where astronauts will receive a chronic low dose from Galactic Cosmic Rays (GCRs) and potentially higher short-term doses from sporadic, unpredictable Solar Energetic Particles (SEPs). GCRs include HZE particles; SEPs typically do not and we therefore exclude them from consideration in this article. Nucleus-nucleus collisions can result in the breakup of heavy ions into lighter ions. In space, this is generally beneficial because dose and dose equivalent are, on the whole, reduced in the process. The GCRs can be considered a radiation field with a significant high-LET component; when they pass through matter, the high-LET component is attenuated, at the cost of a slight increase in the low-LET component. Not only are the standard measures of risk reduced by fragmentation, but it can be argued that fragmentation also reduces the uncertainties in risk calculations by shifting the LET distribution towards one that is more concentrated at low LET, where biological effects are better understood. We review previous work in this area, including measurements made by the Radiation Assessment Detector (RAD) during its journey to Mars and while on the surface of Mars aboard the Curiosity rover.